UJARAN KEBENCIAN DALAM PEMILIHAN UMUM PERSPEKTIF SIYASAH SYAR’IYYAH (STUDI KASUS KABUPATEN SIDRAP) - Mubarak, Muhammad Rezky (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The purpose of this study was to find out the role of the General Election Commission in overcoming forms of acts of hate speech in general elections in Sidrap district. The result of this study is the role of the KPU in overcoming hate speech, namely by working with Bawaslu. Bawaslu reports to the KPU and jointly follows up on cases of hate speech. An example of this is a sympathizer or supporter of one of the candidates for Regent and Deputy Regent satirized (insulted) their political opponents. The law does not discuss cases of hate speech, but the KPU and the Sidrap Regency Bawaslu summoned and followed up on reports regarding hate speech. In the perspective of siyasa syar’iyyah, of course, things like this often happen in general elections, there are insults, provocations, spreading fake news and defamation. Therefore Islam forbids the existence of these actions in everyday life, because it will cause riots and chaos.